PENGARUH MANAJEMEN PERUBAHAN, BUDAYA ORGANISASI DAN KUALITAS KERJA TERHADAP KINERJA PEGAWAI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN CABANG PADANG SIDEMPUAN - Yasmine Ramadhana Harahap (Universitas Islam Sumatera Utara, 2020)
One of the keys to a company's success is to depend on good employee performance and harmoniously intertwined directly or indirectly contribute to offices that include internal and external interests that are owned by offices. For this reason, in improving employee performance, it is necessary to manage changes and organizational culture that can affect performance, because many employees have different attitudes, different cultural backgrounds, and different understandings that can affect employee performance in an organization. For this reason, in improving employee performance, it is necessary to manage changes and organizational culture that can affect performance, because many employees have different attitudes, different cultural backgrounds, and different understandings that can affect employee performance in an organization. Based on the results of the equation, the following explanation can be described: Constant value of 46.243 means that if the overall value of the variable (Management of Change X1, Organizational Culture X2, Quality of Work X3) rises by 1a respectively, the value of Performance (Y) will rise to 46,243. Change Management by 0.220 means that if the Change Management value increases by 1a then the performance value will also increase by 0.220. A positive coefficient value means that Change Management has a positive influence on performance. Organizational Culture coefficient value of 0.543 means that if the Organizational Culture value increases by 1a, the performance value will also increase by 0.543. A positive coefficient value means that Organizational Culture has a positive influence on Performance. The coefficient of Work Quality value of 0.482 means that if the value of Work Quality rises by 1a, the value of performance will also increase by 0.482. A positive coefficient value gives the meaning that Work Quality has a positive influence on Performance.